2020
DOI: 10.1515/cdbme-2020-2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six different marker sets to analyze knee kinematics and kinetics during landings

Abstract: In motion analysis marker sets or protocols are mostly developed for gait analysis and it has been shown that the marker set used affects the results of gait analysis. These marker sets are also used for the analysis of high dynamic sports movements. Single-leg landings are a common tool to investigate functional knee stability and further to predict injury risks where frontal plane motion and loading seem to play an important role. Until now, it is unknown how the marker sets affect the motion analysis result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…Specifically, in the frontal and transverse plane, the differences between the two models were demonstrated for the ROM of Hip Rotation in both groups and Knee Abduction/Adduction in OA patients, the initial joint angle of the Knee Abduction/Adduction and Subtalar Eversion/Inversion in OA patients, Peak Internal Rotation of the Hip Rotation in healthy subjects, Peak Adduction and Peak Abduction of the Knee Abduction/Adduction in OA patients, Peak Internal Rotation and Peak External Rotation of the Knee Rotation in healthy subjects, Peak Inversion in healthy subjects. These findings are comparable with previous studies [ 19 21 , 24 , 29 ]. In previous studies, some researchers found the differences between marker sets at the knee and hip rotation in the transverse plane [ 19 , 24 , 25 , 29 ], while others also found the differences at the knee in the frontal plane [ 24 , 25 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, in the frontal and transverse plane, the differences between the two models were demonstrated for the ROM of Hip Rotation in both groups and Knee Abduction/Adduction in OA patients, the initial joint angle of the Knee Abduction/Adduction and Subtalar Eversion/Inversion in OA patients, Peak Internal Rotation of the Hip Rotation in healthy subjects, Peak Adduction and Peak Abduction of the Knee Abduction/Adduction in OA patients, Peak Internal Rotation and Peak External Rotation of the Knee Rotation in healthy subjects, Peak Inversion in healthy subjects. These findings are comparable with previous studies [ 19 21 , 24 , 29 ]. In previous studies, some researchers found the differences between marker sets at the knee and hip rotation in the transverse plane [ 19 , 24 , 25 , 29 ], while others also found the differences at the knee in the frontal plane [ 24 , 25 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are comparable with previous studies [ 19 21 , 24 , 29 ]. In previous studies, some researchers found the differences between marker sets at the knee and hip rotation in the transverse plane [ 19 , 24 , 25 , 29 ], while others also found the differences at the knee in the frontal plane [ 24 , 25 , 29 ]. In this study, the findings in healthy subjects are in agreement with the former, while the findings in OA patients correspond to the latter.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, valgus angles of approximately 10° to 20° in uninjured controls and approximately 40° during injury scenarios have been reported. 43,67 However, coronal plane angles estimated using motion capture may be variable depending on the chosen marker set 45 and are susceptible to skin motion artifact. 2 With regard to videography, the relative camera position and the flexion angle of the participant’s knee can lead to significant overestimation (~30°) of the resultant coronal plane angles.…”
Section: Discussionmentioning
confidence: 99%
“…55 The difference in reflective marker sets used in various studies can also affect both joint kinematic and kinetic readings, further complicating the comparison of data from different articles. 56…”
Section: Discussionmentioning
confidence: 99%
“…55 The difference in reflective marker sets used in various studies can also affect both joint kinematic and kinetic readings, further complicating the comparison of data from different articles. 56 Although these reviewed studies have shown statistically significant modulations in biomechanical variables with the use of PKBs, it is unknown if the magnitude of these changes are clinically significant in the prevention of ACL injuries in noninjured individuals. There is a paucity of evidence in the current literature to describe minimal clinically important differences (MCID) values for kinematic and kinematic factors in the reduction of ACL injuries.…”
Section: Discussionmentioning
confidence: 99%